2014
DOI: 10.1254/jphs.13184fp
|View full text |Cite
|
Sign up to set email alerts
|

N-Stearoyltyrosine Protects Against Glutamate-Induced Oxidative Toxicity by an Apoptosis-Inducing Factor (AIF)-Mediated Caspase-Independent Cell Death Pathway

Abstract: Abstract. NStearoyltyrosine (NsTyr), a synthesized anandamide (AEA) analogue, could exert potent neuroprotective effects on cerebral ischemia models both in vivo and in vitro via intervening in multiple injuries. Glutamate, a major excitatory neurotransmitter, plays a critical role during stroke/cerebral ischemia. In this study, we explored the protective effects of NsTyr on glutamate neurotoxicity in PC12 cells and investigated its underlying mechanisms. NsTyr treatment attenuated glutamateinduced oxidative t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 43 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…In response to apoptotic stimuli, AIF molecules are released from the mitochondria into the cytoplasm followed by translocation to the nucleus and subsequent integration with chromosomal DNA, which leads to chromosome condensation and DNA breakage into large fragments (~50 kB) (35). AIF exhibits apoptosis-inducing activity and oxidoreductase activity, which result in interlinkage (36). Notably, AIF was the first molecule to be identified that mediates cell apoptosis directly, however, it has also been reported that caspases are involved in AIF apoptotic activity (37).…”
Section: Discussionmentioning
confidence: 99%
“…In response to apoptotic stimuli, AIF molecules are released from the mitochondria into the cytoplasm followed by translocation to the nucleus and subsequent integration with chromosomal DNA, which leads to chromosome condensation and DNA breakage into large fragments (~50 kB) (35). AIF exhibits apoptosis-inducing activity and oxidoreductase activity, which result in interlinkage (36). Notably, AIF was the first molecule to be identified that mediates cell apoptosis directly, however, it has also been reported that caspases are involved in AIF apoptotic activity (37).…”
Section: Discussionmentioning
confidence: 99%
“…20 The neurotoxicity of Glu is mediated largely through influx of calcium through the NMDA receptor, leading to activation of poly(ADP-ribose) polymerase 1 (PARP-1) and generation of poly(ADP-ribose) polymer (PAR polymer), a newly described death signal that kills cells through apoptosis-inducing factor (AIF). [21][22][23] Since broad-spectrum caspase inhibitors fail to prevent PAR polymer-induced cell death, 24 this form of cell death is a caspase-independent process, and has recently been designated parthanatos to distinguish it from the other types of cell death. 6,7 Previous studies reported that erythropoietin (EPO) administered intraperitoneally or intravitreally was protective for both retinal neurons and vascular cells in early diabetes 25,26 ; safety was proven even with high-dose EPO delivered into the eye in both experimental and clinical studies.…”
Section: Figurementioning
confidence: 99%
“…The importance of understanding the mechanisms underlying this process lies in the fact that the majority of patients affected by ischemic insults manifest irreversible events, which in the worst cases make disability, including motor dysfunction, post-stroke dementia and depression thus reducing the REVIEW quality of life. The progress of ischemic damages is determined by several factors including the duration of the ischemic episode and the properties of the affected cells [3][4] . An interruption in cerebral blood flow, which limits oxygen and glucose availability and induces energy depletion, leads to a disturbance in ionic gradients, and thereby a collapse of the membrane potential of neuronal cells, thus causing brain damages that become irreversible if the blood flow is not restored immediately [5][6] .…”
Section: Introductionmentioning
confidence: 99%